Accuracy assessment on the analysis of unbound drug in plasma by comparing traditional centrifugal ultrafiltration with hollow fiber centrifugal ultrafiltration and application in pharmacokinetic study - Zhang, Lin; Zhang, Zhi-Qing; Dong, Wei-Chong; Jing, Shao-Jun; Zhang, Jin-Feng; Jiang, Ye (Journal of Chromatography A, 2013)
•Factors that affect the ultrafiltrate volume were comprehensively investigated.•Ultrafiltrate volume is a crucial factor on the accurate measurement of unbound drug.•The ultrafiltrate volume by HFCF-UF can be easily controlled.•The HFCF-UF method has extremely low detection limit and perfect recovery. In present study, accuracy assessment on the analysis of unbound drug in plasma was made by comparing traditional centrifugal ultrafiltration (CF-UF) with hollow fiber centrifugal ultrafiltration (HFCF-UF). We used metformin (MET) as a model drug and studied the influence of centrifugal time, plasma condition and freeze–thaw circle times on the ultrafiltrate volume and related effect on the measurement of MET. Our results demonstrated that ultrafiltrate volume was a crucial factor which influenced measurement accuracy of unbound drug in plasma. For traditional CF-UF, the ultrafiltrate volume cannot be well-controlled due to a series of factors. Compared with traditional CF-UF, the ultrafiltrate volume by HFCF-UF can be easily controlled by the inner capacity of the U-shaped hollow fiber inserted into the sample under enough centrifugal force and centrifugal time, which contributes to a more accurate measurement. Moreover, the developed HFCF-UF method achieved a successful application in real plasma samples and exhibited several advantages including high precision, extremely low detection limit and perfect recovery. The HFCF-UF method offers the advantage of highly satisfactory performance in addition to being simple and fast in pretreatment, with these characteristics being consistent with the practicability requirements in current scientific research.